Nuptiality trends and fertility transition in Latin America - Rosero Bixby, Luis (1996)
The purpose of this chapter is to determine the role played by nuptiality changes in the fertility transition in Latin America. As other contributions to this book show, most Latin American countries have reduced substantially their fertility since 1960 approximately. In this chapter we examine the extent to which changes in marriage patterns explain this generalized fertility decline. Fertility transition in Europe occurred without the help o f nuptiality changes, or even in spite of a marriage boom (Hajnal 1956; Watkins 1981; Dyson and Murphy 1985). Late age at marriage and widespread spinsterhood had brought about moderate levels of fertility long before the European transition, in what Coale has called a ‘first’ transition (Coale 1973). In developing countries, in contrast, prevalent patterns of almost universal and precocious marriage have suggested that important fertility decline can occur because of nuptiality changes. Several studies have, indeed, showed meaningful effects of marriage changes, particularly in East Asia. For example, Mauldin and Berelson (1978) found that delayed marriages account for 35-40 per cent of birth rate reductions in ten developing countries with major fertility declines. Cho and Retherford (1974) also estimated an important contribution of nuptiality to birth rate declines in seven Asian populations between 1960 and 1970, which range from 23 per cent in Taiwan to 102 per cent in the Philippines. The literature on nuptiality and its effect on fertility in developing countries has been dominated by observations from Asia and tropical Africa, however. Nuptiality and family patterns in Latin America are intermediate between those in Western Europe and those in Asia or Africa (Merrick 1986; De Vos 1987). The female mean age at marriage is 22 years and the proportion of never married women by age 50 is 13 per cent in Latin America as a whole, figures that contrast with, for example, 19 years and 2 per cent respectively in South Asia (United Nations 1988: table 5). Regional trends in Latin American nuptiality and their impact on fertility have not been well documented.